Kontribusi Corporate Social Responsibility Terhadap Peningkatan Soft Skill Dan Digital Skill Tenaga Kerja - Rahel Veronika Siregar; Krisnawati Silaban; Khairani Alawiyah Matondang; Mahlina Putri Manurung; Nadya Nafisah (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
This study aims to analyze the empowerment of human resources (HR) through hard skills training in the digital era and the role of Corporate Social Responsibility (CSR) and the wage system in improving the competitiveness of the Indonesian workforce. The methodology used includes a literature review and secondary data analysis on digital skills training and remuneration conditions in Indonesia. The findings show that digital skills training and improved remuneration systems can increase worker productivity and welfare. Collaboration between the government, companies and communities is essential in supporting the development of competent human resources who are ready to face global challenges.